Customer Perception of Two Leading Footwear Companies in Bangladesh: BATA and APEX (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This research aims to assess customer perceptions of two leading Bangladeshi footwear brands, BATA and APEX. A structured questionnaire was designed to evaluate factors such as price, size, durability, design, and additional benefits influencing consumer beliefs. The study examines how sudden price changes, trust in information sources, aesthetic appeal, and willingness to pay affect customer perceptions. It also segments respondents by age, gender, occupation, monthly income, and preferred brand to gain deeper insights into consumer behavior. Additionally, the research analyzes media and promotional content of BATA and APEX, identifying implicit and explicit messages, characteristic language associated with positive or negative beliefs, and the impact of celebrity endorsements. Comparisons between the two brands are drawn across all examined dimensions, providing a comprehensive understanding of consumer perceptions and preferences in the Bangladeshi footwear market.